Investigation of the Relationship between Food Addiction and Anxiety, Depression and Attention Deficit / Hyperactivity in Obese and Non-Obese: Food Addiction Anxiety Depression Hiperactivity Obese Non Obese - Akcan, Gizem; Uğraş, Seda; Tarı Cömert, Itır; Yükseloğlu, Hülya; İşlek, Dilek; Tutkun, Erkut (Progress in Nutrition, 2021)
The aim of this study is to show the relationship between Attention Deficit Hyperactivity Disorder (ADHD) and food addiction in obese patients. It is thought that obese people have more tendency to have food addiction. Moreover, it is thougt that ADHD is related with food addiction and especially impulsivity subdimension has strong relationship with food addiction. Obesity is one of the biggest health problems common in the world. In this study, it is observed that the variables of age, gender, educational status, marital status and alcohol use and the presence of psychopathological disorders such as anxiety and anxiety are important risk factors for obesity. For this reason, it can be said that by giving priority to women at high risk, organizing prevention and intervention studies for related risk factors will be effective in preventing and controlling obesity. In addition, it can be thought that performing awareness raising and encouraging studies in terms of the importance of healthy eating and regular exercise habits in the fight against obesity will decrease the incidence of obesity.